Oxidized calmodulin kinase II regulates conduction following myocardial infarction: a computational analysis. - Matthew D Christensen; Wen Dun; Penelope A Boyden; Mark E Anderson; Peter J Mohler; Thomas J Hund (PLoS Computational Biology)
Calmodulin kinase II (CaMKII) mediates critical signaling pathways responsible for divergent functions in the heart including calcium cycling, hypertrophy and apoptosis. Dysfunction in the CaMKII signaling pathway occurs in heart disease and is associated with increased susceptibility to life-threatening arrhythmia. Furthermore, CaMKII inhibition prevents cardiac arrhythmia and improves heart function following myocardial infarction. Recently, a novel mechanism for oxidative CaMKII activation was discovered in the heart. Here, we provide the first report of CaMKII oxidation state in a well-validated, large-animal model of heart disease. Specifically, we observe increased levels of oxidized CaMKII in the infarct border zone (BZ). These unexpected new data identify an alternative activation pathway for CaMKII in common cardiovascular disease. To study the role of oxidation-dependent CaMKII activation in creating a pro-arrhythmia substrate following myocardial infarction, we developed a new mathematical model of CaMKII activity including both oxidative and autophosphorylation activation pathways. Computer simulations using a multicellular mathematical model of the cardiac fiber demonstrate that enhanced CaMKII activity in the infarct BZ, due primarily to increased oxidation, is associated with reduced conduction velocity, increased effective refractory period, and increased susceptibility to formation of conduction block at the BZ margin, a prerequisite for reentry. Furthermore, our model predicts that CaMKII inhibition improves conduction and reduces refractoriness in the BZ, thereby reducing vulnerability to conduction block and reentry. These results identify a novel oxidation-dependent pathway for CaMKII activation in the infarct BZ that may be an effective therapeutic target for improving conduction and reducing heterogeneity in the infarcted heart.